Economic Value of Coral Reefs Damage in Negeri Hative Besar, Ambon City - Eygner Gerald Talakua; Rinythanya Kristiani Noya; Johanis Hiariiey (Faculty of Fisheries and Marine Science, Brawijaya University, 2020)
Coral reefs in Negeri Hative Besar, Ambon City are in a bad category or almost lost, where the percentage of coral cover is very small. One form of management for sustainability is to provide economic value for the damage to coral reefs. The purpose of this study was to assess community perceptions, analyze the relationship between perceptions and willingness to pay for repairing damage to coral reefs and to estimate the economic value of coral reef damage. This study uses a survey method. Data analysis consists of an analysis of public perceptions, analysis of the relationship between perceptions and WTP, and analysis of non-market economic valuations. The results showed that the community had knowledge about coral reefs, the benefits of coral reefs, and damage to coral reefs. There is no relationship between perceptions and willingness to pay the community for repairing damage to coral reefs in Negeri Hative Besar. The economic value of damage to coral reefs through a non-market approach in Negeri Hative Besar is IDR 1,188,332.66/month or IDR 14,259,991.95/year. Based on the economic value obtained, the management of coral reef damage in Negeri Hative Besar can be carried out through rehabilitation and coral transplantation activities with the involvement of the local community.